THE EARLY INTERVENTION TENDENCY OF CHINESE CHILDREN WITH COCHLEAR IMPLANTS - Wu, Jiaojiao; Xie, Yuhan (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
From the change of adult unilateral cochlear implantation into young children even under the age of six implant cochlear, sequential bilateral cochlear implantation, which benefit by early hearing screening and technological development of cochlear implants. It is a worldwide trend that simultaneous bilateral cochlear implantation for hearing impaired children under the age of three. Cochlear implants bring changes of education opportunities and choices for children with hearing impairment. Family-centered postoperative early intervention is important, at the same time, hearing impaired children group characteristics tend to be diversified. A growing number of children with cochlear implants study in regular school, consequently, the number of deaf student is decreasing in deaf school. Regular school faces the challenge of lacking of professional teaching staff.